Peningkatan Kemampuan Berfikir Kritis Peserta Didik melalui Penerapan Pendekatan TaRL dan CRT Menggunakan Model Pembelajaran PBL Terintegrasi Teknologi Media Pembelajaran Google Sites - Dela Fitria; Rika Kartika; Susanna R. Harahap (Departement of Mathematics Education, 2024)
Teachers need to design learning in a structured manner so that the goals are achieved effectively. The need for creativity in teaching methods aimed at improving the quality of the learning process. The learning model that provides students with the opportunity to develop critical thinking skills is the Problem Based Learning learning model. Problem Based Learning. One approach that can be chosen to improve students' critical thinking skills on a collaborative basis and through integration of local culture and daily life problems is the Teaching at The Righl Level (TaRl) approach. In line with this, this learning can be connected to academic content in real world situations by combining Culturally Responsive Teaching (CRT) approaches. Furthermore, in the Industrial Revolution 5.0 era, education does not only focus on mastering students' cognitive knowledge but also emphasizes other abilities. One technology that can be integrated into learning, allows collaboration with fellow members, has a responsive website appearance and has strong security is Google Sites (G Sites). This research was carried out using two stages, Cycle I and Cycle II. Based on the results of the descriptive analysis, there was an increase in students' critical thinking within the very good criteria